PENINGKATAN PRESTASI BELAJAR MATEMATIKA PADA MATERI PERSAMAAN GARIS MELALUI METODE THINK PAIR SHARE PADA SISWA SMP - Sepniyanti Sepniyanti; Hawa Liberna; Muhammad Rusdi (Universitas Muhammadiyah Ponorogo, 2018)
Education is a strategic aspect in the development of human resources. Education must also be carried out consistently, which includes innovation, continuous development towards better, proactive and progressive. Teachers who become one of the determinants are expected to be able to use the right learning method. The purpose of this study was to determine the effectiveness of the TPS method (think, pair, share). Data were processed using SPSS 22. Tests were carried out, normality and homogeneity tests and paired t tests. The results obtained show that the TPS method can improve mathematics learning outcomes